Education Maintenance Allowance Transport Pilots – quantitative findings from year 1 and 2 (2000-2001/2001-2002) - Kim Perren; Sue Middleton; Carl Emmerson (2003)
This report contains a summary of quantitative evidence from an evaluation of the Education Maintenance Allowance Transport (EMA(T)) pilots, commissioned by the Department for Education and Skills (DfES).